People power the Philippine experience. (Manila Communication Foundation for Asia, 1986)
A compact, comprehensive and moving documentary that traces the roots of people power from the assassination of ex-senator Benigno "Ninoy" Aquino to the 4-day triumph by the Camp Crame and Camp Aguinaldo in EDSA. Witnessed by the whole world, the four fateful days of February 22-25, 1986 changed the history of the Filipino nation.
Host, Bong Lapira.
Keywords: People power; Philippines -- History -- Revolution, 1986.